Highly Luminescent CB[7]‐Based Conjugated Polyrotaxanes Embedded into Crystalline Matrices. Issue 11 (12th September 2017) - Erdem, Talha; Idris, Muazzam; Demir, Hilmi Volkan; Tuncel, Dönüs
Abstract: π‐Conjugated polymers suffer from low quantum yields (QYs) due to chain–chain interactions. Furthermore, their emission in solid films is significantly quenched due to aggregation leading further decrease in QY. These are the two main issues of these materials hampering their widespread use in optoelectronic devices. To address these issues, here the backbone of poly(9, 9′‐bis(6″‐( N, N, N ‐trimethylammonium)hexyl)fluorene‐ alt ‐ co ‐thiophenelene) is isolated by threading with cucurbit[ 7 ]uril (CB7). Subsequently, the conjugated polyrotaxanes are incorporated into organic crystalline matrices to obtain highly efficient color‐converting solids suitable for solid‐state lighting. Upon threading the polymer backbone with CB7s, although the QY of the resulting polyrotaxane in solution state increases, the quenching problem in their solid state is not completely tackled. To solve this problem, these conjugated polyrotaxanes are embedded into various crystalline matrices and their remarkably high QYs (>50%) in the solution are successfully maintained in the solid state. To demonstrate the suitability of these aforementioned materials for solid‐state lighting, a proof‐of‐concept light‐emitting diode is constructed by employing their powders as color converters. Abstract : Conjugated polyrotaxanes are incorporated into organic crystalline matrices to obtain highly efficient color converting solids suitable for solid‐state lighting.